Contralateral Endoscopic Approach for a Rare Case of Neuroglial Cyst - Singh, Deepak Kumar; Sinha, Kshitij; Singh, Rakesh Kumar; Chand, Vipin Kumar; Singh, Neha; Singh, Arun Kumar; Kumar, Krishan (Indian Journal of Neurosurgery, 2023)
Neuroglial cysts are very rare benign lesions of the brain, accounting for up to 1% of all intracranial cysts. Various intracranial locations such as parenchyma, ventricles, subarachnoid spaces, and rarely the spinal cord have been reported. The clinical features vary according to the site of the cyst ranging from being asymptomatic to having headache, seizures, and hemiparesis. It is most commonly seen in infants and children but can be seen in adults too. This rare case is of a middle-aged woman presenting with complaints of headache and left-sided hemiparesis. We report a rare case of a right-sided neuroglial cyst for which a contralateral endoscopic approach was taken for the surgery. Endoscopic cyst fenestration is an ideal modality to treat neuroglial cyst. The contralateral endoscopic approach to treat neuroglial cyst is a better option with the advantage of minimal invasiveness along with better visualization of ventricles and easy maneuverability of the endoscope within the ventricles and surrounding anatomy.
Keywords: neuroglial cyst; neuroepithelial cysts; glioependymal cysts; contralateral approach; endoscopic; navigation guided